2012
DOI: 10.1590/s1415-52732012000600001
|View full text |Cite
|
Sign up to set email alerts
|

Alterações bioquímicas e hepáticas em ratos submetidos à uma dieta hiperlipídica/hiperenergética

Abstract: OBJETIVO: O presente estudo teve como objetivo analisar as alterações bioquímicas hepáticas decorrentes da administração de uma dieta hiperlipídica/hiperenergética em ratos. MÉTODOS: Foram utilizados 20 ratos (Wistar) com 90 dias de idade divididos em dois grupos, grupo-controle constituída por ratos eutróficos alimentados com dieta comercial para roedores e grupo-dieta constituída por ratos submetidos a uma dieta hiperlipídica/hiperenergética semi purificada feita com 35% de gordura sendo 31% de origem animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
4
0
5
Order By: Relevance
“…It is suggested that the animals are able to regulate their feed intake by the total consumed energy [16,17,18]. The same was observed in the study by [19], they observed lower dietary intake in the group that received diet rich in fat compared to the group that consumed balanced diet. In the present study, we observed lower feed intake of animals from JG and WG.…”
Section: Discussionmentioning
confidence: 52%
“…It is suggested that the animals are able to regulate their feed intake by the total consumed energy [16,17,18]. The same was observed in the study by [19], they observed lower dietary intake in the group that received diet rich in fat compared to the group that consumed balanced diet. In the present study, we observed lower feed intake of animals from JG and WG.…”
Section: Discussionmentioning
confidence: 52%
“…According to LANGE et al (2005) and MOURA et al (2012), the accumulation of fat in the abdominal region must be carefully monitored, as this increase is considered a determining factor in the development of insulin resistance, also because the abdominal adipose tissues are metabolically more active than the peripheral adipose tissues. After replacing soybean oil with extra virgin coconut oil in both diets, was observed a reduction in peritoneal fat and lower food intake in the hyperlipidic groups, but no significant differences were noted in the weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…Nas últimas décadas, têm ocorrido, de forma mundial, modificações dos hábitos das pessoas de todas as faixas etárias, que apresenta uma grande preferência por alimentos de baixo custo e uma alta palatabilidade 1 . Os alimentos denominados "fast food" e ultraprocessados, geralmente fornecem baixa qualidade nutricional e uma grande quantidade de calorias oriundas dos carboidratos e lipídios 2 , que juntamente com o sedentarismo aumenta a incidência das Doenças Crônicas Não Transmissíveis, como a obesidade 2,3 .…”
Section: Introductionunclassified
“…A obesidade, que é caracterizada pelo excesso de tecido adiposo, pode acarretar a resistência à insulina e à leptina, dificultando a entrada de glicose em algumas células, sendo que tal fato aumentará a hidrólise dos triacilgliceróis, que sobrecarregará o fígado e poderá gerar a esteatose hepática 2,7,8 , que é a manifestação inicial da Doença Hepática Gordurosa Não Alcoólica (DHGNA). O acúmulo dos lipídios no fígado é chamado de Doença Hepática Gordurosa Não Alcoólica, e quando não tratada pode progredir para a cirrose hepática ou câncer 2,8,9,10 .…”
Section: Introductionunclassified